Pengaruh Penambahan Tepung Sagu Pada Yoghurt Terhadap Viskositas, Overrun, Kecepatan Meleleh dan Total Padatan Es Krim Yoghurt - Ika Ayu Wijayanti; Purwadi Purwadi; Imam Thohari (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2015)
The purpose of this research was to find out the best concentration of adding sago flour in yoghurt based on viscosity, overrun, melting rate and total solid of yoghurt ice cream. The experiment was designed by Completely Randomized Design (CRD) using four treatments were 0 %, 2 %, 4 %, 6 % from volume of fresh milk and four replication. The data were analyzed by using Analysis of Variance (ANOVA) and continued by Duncan’s Multiple Range Test (DMRT). Result of this research showed that concentration of adding sago flour in yoghurt gave highly significant difference effect (P<0.01) on viscosity, overrun, melting rate and total solid of yoghurt ice cream. It can be concluded that the adding of sago flour 2% in yoghurt gave the best result with the viscosity was 1750.75 cP, overrun was 25.14%, melting rate was 39.13 minutes/50 g, total solid was 36.20% and gave the best quality of yoghurt ice cream.